Do as Essay, Not as I Do? How Inflated List Prices of Unsold Essayer Homes Affect the Price Discovery Process - Sumit Agarwal; Michael J. Seiler; Ralph Siebert (Center for Economic Studies and ifo Institute (CESifo), 2022)
In the U.S. real estate market, around 30 percent of listed properties remain unsold. We examine whether unsold property listings exert externalities in the housing market. Our study builds on a comprehensive dataset that encompasses residential property listings in Orange County (California) from 2000 to 2020. We find that listed properties often remain unsold because speculative owners (also referred to as essayers) make attempts to sell properties for prices far above fair market value (on average, by 59,576 or 8.1 percent). Our results show that overpriced (unsold) listings exert spillover effects that distort and inflate housing prices. They increase other properties' list prices on average by 40,180 (5.5 percent) and increase sale prices by 37,268 (5.2 percent). We find that sale prices further increase with spillover effects for homes with specific housing and neighborhood attributes (such as large house size, high-income areas, and close proximity to beach, coastal, and central city areas). Overpriced unsold properties cause annual extra earnings (or extra spending) of almost 1 billion in Orange County (California) alone. We also find that the extent of overpricing depends on the economic environment, that is, overpricing is higher (lower) during booms (busts).
Keywords: R30; L10; L60; O30; 330; essayers; hedonic pricing; housing market; spillover effects; unsold properties